Antecedents of Capital Structure Registered Companies on the Lq-45 Index on the Indonesia Stock Exchange 2014-2017 - Denny Mahendra; Lestiyani Lestiyani (STIE AUB Surakarta, 2019)
This study aims to determine the empirical evidence that determines the capital structure of Manufacturing Companies Listed on the Indonesia Stock Exchange in 2014 to 2017. The research design using the causal method is ex post facto. The population in this study are all companies that are listed in the LQ-45 index on the Indonesia Stock Exchange in 2014-2017. The samples in this study are company data available in the Indonesian Capital Market Directory (ICMD) in 2014-2017 as many as 25 companies. The results showed that there were four hypotheses which proved to have a significant effect on the company's debt ratio value. First, company growth (growth) had a significant effect on the company's debt ratio value (= 0.011; tcount = 2.699; 0.008 <0.05); second, the results of the study show that the profitability proxied by CR shows a significant negative effect (= -0,001; thitung = -2,600; 0,010 <0,05; Third, there is a significant and negative relationship between size and debt ratio (= 0,164; thitung = 2,039; 0,044 <0,05. So the third hypothesis in this study is proven. ROE has a significant effect on the debt ratio (= 0,020; thitung = 21,424; 0,000 <0,05).